Visual estimation of blood loss versus quantification of blood loss after vaginal birth using an innovative drape: a prospective study - Mishra, Nalini; Dhruw, Suman; Mishra, Ishan; Daharwal, Abha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: This study was done to compare the accuracy of visual estimation of blood loss (EBL) and quantitative assessment of blood loss (QBL, sum of volumetric and gravimetric assessment) against a reference standard i.e. calculated QBL (C-QBL) and also with each other after vaginal birth. Methods: Prospective observational cohort study conducted at Pt. JNM medical College Raipur, Chhattisgarh, India and involved 101 low risk women after vaginal birth. Women were allocated alternately to EBL or QBL group (volumetric component of measured blood loss was done with an innovative low cost drape prepared with a plastic apron at the point of care. Gravimetric component was measured by weight difference of the mops and pads before and after use). C-QBL was calculated for each case with a standard formula. Main outcome measure was comparing the correlation coefficient of EBL and QBL each with C-QBL. Results: The mean blood loss in 51 women of EBL group and 50 women of QBL group was 275.29 ml and 380 ml respectively. Pearson’s correlation coefficient (r) of EBL with C-QBL was 0.4984 (weak correlation) compared to that of QBL with C-QBL (r=0.9093, strong positive correlation). The error of underestimation by EBL compared to QBL was 28% (mean=104.71 ml p<0.0001). The relative risk (RR) of underestimating blood loss of >500 ml by EBL method was 5 (95% CI .605-41.3). Conclusions: Visual EBL should be replaced with QBL for measurement of postpartum blood loss. Using innovative under-buttock low cost drape greatly helps in routine QBL.